A Decision Theoretic Approach to Data Leakage Prevention - MARECKI, Janusz (Institutional Knowledge at Singapore Management University, 2010)
In both the commercial and defense sectors a compelling need is emerging for rapid, yet secure, dissemination of information. In this paper we address the threat of information leakage that often accompanies such information flows. We focus on domains with one information source (sender) and many information sinks (recipients) where: (i) sharing is mutually beneficial for the sender and the recipients, (ii) leaking a shared information is beneficial to the recipients but undesirable to the sender, and (iii) information sharing decisions of the sender are determined using imperfect monitoring of the (un)intended information leakage by the recipients.We make two key contributions in this context: First, we formulate data leakage prevention problems as Partially Observable Markov Decision Processes; we show how to encode one sample monitoring mechanism—digital watermarking—into our model. Second, we derive optimal information sharing strategies for the sender and optimal information leakage strategies for a rational-malicious recipient as a function of the efficacy of the monitoring mechanism. We believe that our approach offers a first of a kind solution for addressing complex information sharing problems under uncertainty.